Articulation of Hadith in Minangkabau Socio-Religious Contexts: A Study on the Collection of Speeches by Sheikh Abdul Lathif Syakur (1882-1963) - Wendry, Novizal; Hidayat, Ahmad Taufik; Ananda, Yassinta; Azizah, Faras Puji; Hasan, Melati Amanah (Millah: Journal of Religious Studies, 2024)
The collection of speeches (CoS) written by Sheikh Abdul Lathif Syakur (SALS), a scholar who experienced both the colonial and old-order eras, serves as a thematic compilation of hadith reflecting the mid-20th century Minangkabau writing tradition. Through this collection, SALS demonstrated his expertise as a hadith scholar by analyzing the context of his era and interpreting social realities based on hadiths pertinent to society. This article aims to delve into the socio-religious vision that SALS constructs through the themes articulated in his speeches. Using a descriptive-historical method and thematic analysis, this article reveals that SALS founded his socio-religious vision on four main pillars: renewal, community integrity, moderation, and the roles of women in public life. SALS's ability to adapt hadith to his time, combined with his inclusive and human-centered approach, portrays him as a progressive scholar, challenging the rigid stereotype of hadith scholars.